2013
DOI: 10.1038/ng.2649
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypomethylation within specific transposable element families associates with tissue-specific enhancer landscape

Abstract: Introduction Transposable element (TE) derived sequences comprise half of our genome and DNA methylome, and are presumed densely methylated and inactive. Examination of the genome-wide DNA methylation status within 928 TE subfamilies in human embryonic and adult tissues revealed unexpected tissue-specific and subfamily-specific hypomethylation signatures. Genes proximal to tissue-specific hypomethylated TE sequences were enriched for functions important for the tissue type and their expression correlated stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
197
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(216 citation statements)
references
References 60 publications
18
197
0
1
Order By: Relevance
“…Genome-wide DNA methylation studies have found that ERV-9 LTRs (aka LTR12s) are predominantly hypermethylated in multiple human tissues; however, a small portion of them (»14%) are hypomethylated in transcriptionally active gene loci in nucleated blood cells, indicating that LTR hypomethylation is correlated with tissue-specific transcription of the cis-linked genes but LTR hypermethylation is associated with inactive genes. 33 The ERV-9 LTR in the b-globin gene locus was not found among those hypomethylated LTRs in blood cells, which is consistent with our finding that the b-globin ERV-9 LTR was hypermethylated in blood erythroid cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Genome-wide DNA methylation studies have found that ERV-9 LTRs (aka LTR12s) are predominantly hypermethylated in multiple human tissues; however, a small portion of them (»14%) are hypomethylated in transcriptionally active gene loci in nucleated blood cells, indicating that LTR hypomethylation is correlated with tissue-specific transcription of the cis-linked genes but LTR hypermethylation is associated with inactive genes. 33 The ERV-9 LTR in the b-globin gene locus was not found among those hypomethylated LTRs in blood cells, which is consistent with our finding that the b-globin ERV-9 LTR was hypermethylated in blood erythroid cells.…”
Section: Discussionsupporting
confidence: 81%
“…27,[29][30][31] Indeed, over 80% of human lncRNAs contain retrotransposon sequences, among which the LTR sequences are represented disproportionately, 32 indicating prevalent transcriptional activities of the LTR retrotransposons, even though the LTRs are predominantly hypermethylated in the human genome. 33 To investigate the apparent paradox of hypermethylationmediated transcriptional silencing and widespread transcriptional activities of the LTR retrotransposons, we examined the DNA methylation status and the transcriptional activity of an intergenic ERV-9 LTR retrotransposon in the b-globin gene locus in human erythroid cells that transcribe high levels of globin genes. The solitary ERV-9 LTR retrotransposon is located near the 5 0 border of the locus control region (LCR), 40-70 kb upstream of the fetal g-and adult b-globin genes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, on average 20% of TFBS are associated with TEs in human embryonic stem cells (Kunarso et al, 2010). Furthermore, many TFBS derived from TEs are epigenetically regulated by DNA methylation, which has important implications for tissue-specific gene functions in humans (Xie et al, 2013). This indicates that TEs can mutate or introduce TFBS to shape new gene regulatory networks (Figure 2).…”
Section: Te-derived Transcription Factor Binding Sites Can Rewire Regmentioning
confidence: 99%
“…We have recently shown that LTRs are massively transcribed in embryonic stem cells and iPS cells, some of which are involved in the maintenance of pluripotency (Fort et al 2014). Other studies demonstrated a high activity of distinct LTR subfamilies in stem cells using several different methods, including RNA-seq (Kelley and Rinn 2012;St Laurent et al 2013), DNase-seq (Jacques et al 2013), and MeDIP-seq (Xie et al 2013). Furthermore, an appropriate activation of LTRs is essential for iPS reprogramming (Lu et al 2014;Ohnuki et al 2014), suggesting that the expression of LTRs might be associated with cancerous features, such as poor differentiation and high proliferation potency.…”
mentioning
confidence: 99%